(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Tyre is rubber member that provides cushion against the shocks and support load. Tyre is waste material which cause many environmental effects in all the parts of the world representing very serious threat to ecology. One of the possible solutions for the use of scrap tyre rubber is to incorporate it into concrete, to replace some of the natural aggregate. Waste rubber tyre is one of the significant environmental problems worldwide. The waste tyres rubber is not easily biodegradable even after long-period of landfill treatment. The land filing of waste tyre creates soil and water pollution, because the waste tyre rubber holds toxic and soluble components. Burning of tyres results in serious fire hazards and produce many harmful gases. Due to rapid increase in waste tyres many countries banned the disposal of waste rubber tyre in landfills. Hence, the civil engineering use the waste tyres in projects .Rubber tyre c are a waste material that is ideal for use in concrete applications. This has an additional advantage of saving in natural aggregates used in production of concrete which are becoming increasingly scarce. In this essence, our present study aims to use of waste rubber tyre as partial replacements of rubber (10,20,30%) with coarse aggregate. Ordinary Portland cement (OPC) and natural aggregates, which are the key constitutes of concrete, are suggested to recycled or substituted in order to address the sustainability concern. Here by product have been targeted to reduce carbon footprints. Fly ash is a by-product at thermal power stations. An industrial by-product may be inferior to traditional materials used construction applications, but, the lower cost of these inferior materials make it an attractive alternative if adequate performance can be achieved. The use of fly ash is accepted worldwide due to saving in cement, consuming industrial waste and making durable or workable materials, especially due to improvement in the quality fly ash products.